2020
DOI: 10.1177/1066480720964713
|View full text |Cite
|
Sign up to set email alerts
|

“When You Take This Jump and Cross Racial Boundaries”: Parents’ Experiences of Raising Multiracial Children

Abstract: This qualitative study explored the lived experiences of eight parents of multiracial children. Primary themes emerged from the analysis include (a) fostering a child’s multiple heritages, (b) nurturing the whole person, (c) race-conscious parenting, (d) having open communication, (e) learning on the job, and (f) a multidimensional approach to self-care. The findings revealed that parents valued open communication with their children and made efforts to not only connect them with their racial and cultural root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 15 publications
(22 reference statements)
2
4
0
Order By: Relevance
“…The finding supports previous research by Seto et al (2021) who found that parents of multiracial children made great efforts to expose their children to various parts of the parents' ethnic/racial heritage. Additionally, research has shown that it is important for parents of multiracial children to expose their children to their minoritized ethnic/racial side (Rosen & Greif, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The finding supports previous research by Seto et al (2021) who found that parents of multiracial children made great efforts to expose their children to various parts of the parents' ethnic/racial heritage. Additionally, research has shown that it is important for parents of multiracial children to expose their children to their minoritized ethnic/racial side (Rosen & Greif, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in their work on raising multicultural awareness through family therapy, McDowell et al (2005), spoke of ERI achievement through a multiracial person's self-emancipation from internalized racial myths and cultural constraints that maintain the hegemony of inequality. Typically, parents have racially labeled their children based on their own sociopolitical viewpoints where racist rules may determine racial group membership (Rockquemore et al, 2006;Seto et al, 2021). Non-white parents tend to induct their multiracial child's racial socialization and experiences as similar to their own (Crawford & Alaggia, 2008;Nuttgens, 2010;Stone & Dolbin-McNab, 2017).…”
Section: Eri In the Homementioning
confidence: 99%
See 3 more Smart Citations